Integrated B. Ed Programme Implemented in Teacher Education in Respect To NEP-2020 (International Journal of Scientific Research in Science and Technology, 2024)
A teacher is considered as the most creative and unique person as because a teacher has the capability to influence and motivate students through his intellect, ideals, experience , wisdom and dynamic personality and for this reasons teachers are considered a true architect of a nation. India is blessed to have extraordinary educationist like Charaka, Susruta, Aryabhata, Varahamihira, Chanakya, Panini, Patanjali, Nagarjuna, Gautama, Sankardev, Maitreyi, Gargi, Thiruvalluvar etc. are few notable gurus; who have not only enlightened India but also illuminated whole world and the entire world is indebted to their lessons. It has been rightly pointed out by the Education Commission (1964-65) that “The destiny of India is being shaped in her classroom”. After independence Government of India had given special attention towards education sector and set up various committees and commissions, however still India lags behind other countries in respect to teacher education. To overcome this National Council for Teacher Education (NCTE), under the Ministry of Education has recently introduced the National Education Policy 2020; where a lot of new rules are announced for successful implementation of Integrated Teacher Education Programme. Four Year Integrated B.Ed. Programme is a uniquely designed four years integrated programme which involves a holistic bachelor’s degree offering B.A. B.Ed. / B. Sc. B. Ed. and B.Com Four Year Integrated B.Ed. Programme will be helpful for those students who want to join teaching profession in future. Four Year Integrated B.Ed. Programme will be offered by the multidisciplinary institutions and it will be the minimum requisite qualification to become a school teacher. However successful implementation of Four-Year Integrated B.Ed. Programme is a real challenge for the institutions and institutions must prepare strategies for successful implementation of Four Year Integrated B.Ed. Programme in their respective institutions. This paper tries to focus about the strategies, challenges and future prospects of Integrated Teacher Education Programme in respect to NEP 2020.